Interferon γ and Its Important Roles in Promoting and Inhibiting Spontaneous and Therapeutic Cancer Immunity - Alspach, Elise; Lussier, Danielle M; Schreiber, Robert D (Cold Spring Harbor perspectives in biology, 2019)
Originally identified in studies of cellular resistance to viral infection, interferon (IFN)-γ is now known to represent a distinct member of the IFN family and plays critical roles not only in orchestrating both innate and adaptive immune responses against viruses, bacteria, and tumors, but also in promoting pathologic inflammatory processes. IFN-γ production is largely restricted to T lymphocytes and natural killer (NK) cells and can ultimately lead to the generation of a polarized immune response composed of T helper (Th)1 CD4 T cells and CD8 cytolytic T cells. In contrast, the temporally distinct elaboration of IFN-γ in progressively growing tumors also promotes a state of adaptive resistance caused by the up-regulation of inhibitory molecules, such as programmed-death ligand 1 (PD-L1) on tumor cell targets, and additional host cells within the tumor microenvironment. This review focuses on the diverse positive and negative roles of IFN-γ in immune cell activation and differentiation leading to protective immune responses, as well as the paradoxical effects of IFN-γ within the tumor microenvironment that determine the ultimate fate of that tumor in a cancer-bearing individual.